Courtship practices in cases of selected lesbian college students in Metro Manila - Bassig, Roan Shayne B.; Dapiton, Jamey Andrea Lim.; Agustin, Estrella R. (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT The purpose of the study is to describe the courtship practices among lesbian adolescents through the phases of courtship, identify the difficulties they encounter, and determine the strategies on how they deal with these difficulties during the courtship process. The sample was selected among 17-21 year old lesbian college students in Metro Manila who act as the pursuer in the relationship. A total of 30 respondents were subjected to an in-depth face-to-face interview conducted by the researchers. After gathering the results, the researchers have identified four phases of lesbian courtship namely 1) initiating interaction, 2) getting to know, 3) forming intimacy and 4) formalization of the relationship. Difficulties were also identified as well as their coping strategies throughout the courtship process. On the basis of the results of this research, it was revealed that the phases of courtship showed how lesbian adolescents adjust their courtship strategies according to the difficulties they encounter with their personal concerns and immediate environment. The peers of the lesbians have a more significant role than the family in assisting the lesbians with courting and helping them overcome their problems. Finally, the research results showed that lesbian courtship practices are geared towards emotional dependency as opposed to sexual satisfaction in heterosexual courtship.
Thesis (BSFLCD)--University of the Philippines Diliman.
Keywords: Lesbians -- Philippines; Courtship -- Philippines